SOME ISSUES CONCERNING JURISDICTION ON CLAIMS FOR PRELIMINARY RELIEF FOR INFRINGEMENT OF INTELLECTUAL PROPERTY RIGHTS - Paul-George BUTA (Challenges of the Knowledge Society)
The article deals with some issues surrounding the assertion of jurisdiction on claims for preliminary or provisional relief for infringement of intellectual property rights in Romania. Starting with the sources of the national provisions on provisional measures which were the result of implementation of international and EU law, the article then analyzes the relvant provisions in both the Code of Civil Procedure and the laws concerning the protection of intellectual property rights. In the very end, some more strange possible factual situations are analyzed in order to demonstrate the need for further legislative and judiciary guidance on the matter.